2001
DOI: 10.1038/sj.onc.1204185
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of G proteins by covalent modification

Abstract: Heterotrimeric G protein a,b, and g subunits are subject to several kinds of co-and post-translational covalent modi®cations. Among those relevant to G proteincoupled receptor signaling in normal cell function are lipid modi®cations and phosphorylation. N-myristoylation is a co-translational modi®cation occurring for members of the G i family of Ga subunits, while palmitoylation is a post-translational modi®cation that occurs for these and most other Ga subunits. One or both modi®cations are required for plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
176
0
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(188 citation statements)
references
References 95 publications
7
176
0
5
Order By: Relevance
“…We studied the small GP family, checking for effective myristoylation of these proteins. We chose to study the small GP superfamily for the following reasons: (i) genome annotation is simple because of known similarities in sequence characteristics, for GTP binding, for instance (32)(33)(34), and (ii) the members of one of its five distinct families (RAS, RAB, RHO, ARF, and RAN), the ADP-ribosylation factor (ARF) family, are almost systematically N-myristoylated (35). Consistent with the most recent report on this topic (36), we were able to identify 94 genes encoding GP in A. thaliana, although we did also detect an additional ARF (ARFE; At2g24765) (see Fig.…”
Section: Study Of the Complete Set Of Small G Proteins N-myristoylatementioning
confidence: 99%
“…We studied the small GP family, checking for effective myristoylation of these proteins. We chose to study the small GP superfamily for the following reasons: (i) genome annotation is simple because of known similarities in sequence characteristics, for GTP binding, for instance (32)(33)(34), and (ii) the members of one of its five distinct families (RAS, RAB, RHO, ARF, and RAN), the ADP-ribosylation factor (ARF) family, are almost systematically N-myristoylated (35). Consistent with the most recent report on this topic (36), we were able to identify 94 genes encoding GP in A. thaliana, although we did also detect an additional ARF (ARFE; At2g24765) (see Fig.…”
Section: Study Of the Complete Set Of Small G Proteins N-myristoylatementioning
confidence: 99%
“…Mechanisms underlying the PM targeting of the ␣ subunit have been studied in some detail (1)(2)(3). The available data suggest a model in which myristoylation and/or binding to ␤␥ subunits constitutes an initial membrane targeting signal for the ␣ subunit.…”
mentioning
confidence: 99%
“…It showed the highest similarity to G protein α subunits of G i class, Gα i . The candidate sequence for N-terminal myristoylation (MGxxx(S/T)), characteristic for Gα i (Chen and Manning, 2001), was conserved in N-terminal region of HrGα n , indicating that the HrGα n belongs to Gα i class (Fig. 1B).…”
Section: Resultsmentioning
confidence: 99%
“…The deduced amino acid sequence of HrGα n (357 amino acids) showed higher similarity to human G i and G o . There was a candidate sequence for palmitoylation in the N-terminal region of HrGα n , which is conserved in Gα i (Chen and Manning, 2001). The phylogenetic tree constructed based on the deduced amino acid sequence clearly showed that HrGα n is a member of Gα i .…”
Section: Discussionmentioning
confidence: 99%